Effect of Molarity on Double Layer Photocatalytic Activity ZnO/ZnO:Ag for Metanil Yellow Degradation - Anggita, Sheilla Rully; Kusuma, Hamdan Hadi; Sumarti, Heni; Teke, Sosiawati (Faculty of Science and Education, UIN Walisongo Semarang, 2023)
Double layer (DL) ZnO/ZnO:Ag has been synthesized with variations in molarity of 0.1, 0.3, 0.5, and 0.7 M and its application as a degrading agent for methanil yellow dye. This study aims to determine the effect of the molarity of the DL ZnO/ZnO:Ag on crystallinity and photocatalytic activity for methanil yellow degradation. DL ZnO/ZnO:Ag was synthesized using sol-gel technique and deposited with spray coating technique. The results of DL ZnO/ZnO:Ag were characterized by XRD to determine the crystallinity and particle size. The photocatalytic activity was carried out by immersing the DL ZnO/ZnO:Ag layer in 10 ppm methanil yellow solution and irradiating it with UV light for 4 hours and then tested using UV-Vis spectroscopy to get the percentage of methanil yellow degradation. The results showed that the crystallinity of the DL ZnO/ZnO:Ag for all molarity variations had a hexagonal wurtzite structure. Grains size increase as molarity increases from 0.1 to 0.5 M. However, if the concentration continues to be increased to 0.7M, the grain size decreases. Photocatalytic activity is increasing every hour, as indicated by the increasing percentage of degradation. Precursor in 0.5 M has the maximum percentage of degradation is 25.32%.